Animalidade como figura ontológica da subjugação - Caselas, António J. (Trabalhos de Antropologia e Etnologia, 2020)
Subjugation as a political or ethico-political category presents traits that stand comparison to the violence that marked the archaic determination of law and religions. Subjugation has revelead its unconditioned character while molding itself to current configurations which our thought needs to seize. Its analysis has allowed for blurring artificial divides and frontiers opposing the public and private spheres, the social and the individual. We have come to know its ontological radiation apart from its factual/historical contexts. In its realization, we are faced with the negative use of animality and of the relations among human beings. Therefore, the determination of what belongs to the anthropological sphere and what emanates from